Future of the novel - Day, Daisy (My University, 1895)
Introduction: The word novel calls to the minds of most people a world of trashy fiction – stories of wildest exaggeration of love and sensation – tales in which all women were Madonna’s, and all men brave, handsome knights or princes. In these ideal stories, love, happiness, and sunshine held array forever, and at the close of the book we find that “Our hero and heroine lived happy ever after.”
Citation: Day, Daisy. Future of the novel. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Novel; Madonna's; Princes; Knights; Trashy fiction; Theses; Manuscripts (documents)